Pandan Civet Conservation: A Sustainable Business Opportunity for Educational Tourism: Konservasi Musang Pandan : Peluang Bisnis Yang Berkelanjutan Untuk Wisata Edukasi - Salma Rizky Awalya; Azza Silviatul Rochmah; Fevi Firdausi; Maryam Rizka; Rifdah Abadiyah (Procedia of Social Sciences and Humanities, 2026)
General Background: Indonesia holds a strategic global position in coffee production and agritourism development. Specific Background: Kopi Luwak Cikole in Lembang, West Java, operates as an ethical civet coffee enterprise founded by a veterinarian to integrate animal welfare with agricultural tourism. Knowledge Gap: Prior research frequently isolates green business practices, animal welfare, and civet coffee production without comprehensively examining how single-species conservation, selective-scale management, and conventional marketing strategies collectively foster sustainable competitive advantage. Aims: This qualitative case study analyzes the holistic implementation of green business principles, common palm civet conservation, and conventional marketing at Kopi Luwak Cikole. Results: Findings demonstrate that integrated operational pillars—comprising animal welfare-based coffee production, civet conservation, and socio-environmental education—allow the enterprise to maintain premium competitiveness independently of digital platforms. Novelty: This study establishes that authentic green business models in wildlife-based agribusiness can simultaneously generate economic value, support wildlife conservation, and utilize conventional marketing frameworks. Implications: Agribusiness practitioners can replicate ethical production standards and transparency-driven engagement to secure consumer trust and long-term sustainability. Highlights: Common palm civet conservation serves as an ethical and scientific foundation for sustainable agritourism. Selective-scale management combined with conventional marketing maintains premium market positioning without digital platforms. Integrated operational pillars align economic profitability with wildlife protection and socio-environmental education. Keywords: Civet Conservation, Sustainable Business, Educational Agritourism, Animal Welfare, Conventional Marketing